2020
DOI: 10.1002/ps.5811
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of pesticide residues in the topsoil of Belgian fruit orchards: terrestrial environmental risk assessment

Abstract: BACKGROUND Pesticides are widely used in fruit orchards. In the context of integrated pest management (IPM) Flemish farmers are advised to restrict the use of pesticides. However, pesticide residues could still pose a threat to beneficial organisms. To date, it is not well known which residues are present in IPM orchards. This study focuses on the pesticide concentration in the topsoil and the implications for soil‐dwelling organisms. RESULTS Topsoil was sampled in ten sweet cherry (Prunus avium (L.) L.) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, another 16 compounds (27 %) are in the moderately hazardous category (II). The 37 % of the products show some degree of toxicity to bees; this constitutes an important environmental risk factor, which can lead to a decrease in bee populations and thus to a decrease in the role of bees in ecosystems (Claus et al, 2021;Claus & Spanoghe, 2020;Fevery et al, 2016). It is also observed that 71 % of the a.i., have some degree of toxicity in fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another 16 compounds (27 %) are in the moderately hazardous category (II). The 37 % of the products show some degree of toxicity to bees; this constitutes an important environmental risk factor, which can lead to a decrease in bee populations and thus to a decrease in the role of bees in ecosystems (Claus et al, 2021;Claus & Spanoghe, 2020;Fevery et al, 2016). It is also observed that 71 % of the a.i., have some degree of toxicity in fish.…”
Section: Discussionmentioning
confidence: 99%
“…The solvent change is different in the samples for liquid chromatography with mass spectrometry detector (LC-MS/MS) compared to gas chromatography with electron capture detector (GC-ECD) (Claus & Spanoghe, 2020). In the case of LC-MS/MS 1 mL is taken from the top layer of the tube is added to a 10 mL volumetric vial; 9 mL of Milli-Q water is added to the 10 mL vial.…”
Section: Procedures To Analyze Tobacco Crop Samplesmentioning
confidence: 99%
“…These are possibly residues of insecticides applied more than 2 years ago, for which we could not find application records. Indeed, Claus and Spanoghe (2020) found both current and previous sprayed pesticides in the topsoil of sweet cherry and apple orchards. Applied insecticides are lost from the soil surface to the atmosphere with evaporation of water, photolysis, and hydrolysis, and into the soil, where they are degraded by soil microorganisms (Fenner et al, 2013; Kobayashi, 2000), but the speed of this process varied among insecticides as well as the soil types.…”
Section: Discussionmentioning
confidence: 99%
“…Aangezien er in een recente studie uit de EPA ECOTOX-database voor acht pesticiden SSD's zijn gecreëerd voor bodemorganismen op basis van LC50-waardes (Claus et al, 2020), zouden deze type eindpunten een keuze kunnen zijn voor herziene samenvoeging van eindpunten met NTA-soorten. Het filteren op NOEC-of NOEL-eindpunten lijkt een verruiming van de beschikbare NTA-soorten te hebben opgeleverd ten opzichte van eindpunten op basis van 50%-effect, maar lijkt voor meerdere stoffen een beperking te zijn om voldoende eindpunten voor bodemfauna te verkrijgen.…”
Section: Lambda-cyhalothrin En Deltamethrinunclassified